Coupling traction force patterns and actomyosin wave dynamics reveals mechanics of cell motion. Issue 12 (13th December 2021) - Ghabache, Elisabeth; Cao, Yuansheng; Miao, Yuchuan; Groisman, Alex; Devreotes, Peter N; Rappel, Wouter‐Jan
Abstract: Motile cells can use and switch between different modes of migration. Here, we use traction force microscopy and fluorescent labeling of actin and myosin to quantify and correlate traction force patterns and cytoskeletal distributions in Dictyostelium discoideum cells that move and switch between keratocyte‐like fan‐shaped, oscillatory, and amoeboid modes. We find that the wave dynamics of the cytoskeletal components critically determine the traction force pattern, cell morphology, and migration mode. Furthermore, we find that fan‐shaped cells can exhibit two different propulsion mechanisms, each with a distinct traction force pattern. Finally, the traction force patterns can be recapitulated using a computational model, which uses the experimentally determined spatiotemporal distributions of actin and myosin forces and a viscous cytoskeletal network. Our results suggest that cell motion can be generated by friction between the flow of this network and the substrate. SYNOPSIS: A combination of imaging and computational modeling is used to investigate the traction force patterns and the distribution of actin and myosin in three different modes of migration in Dictyostelium discoideum cells. The wave dynamics of actin and myosin critically determine the traction force patterns, cell morphology, and migration modes. Two types of keratocyte‐like motion are observed, consistent with two different propulsion mechanisms. A computational model reveals that cell motion can be generated by friction between the flow of the cytoskeletal network and the substrate. Abstract : A combination of imaging and computational modeling is used to investigate the traction force patterns and the distribution of actin and myosin in three different modes of migration in Dictyostelium discoideum cells.